Neogergithoides, a new genus with a new species from China (Hemiptera: Issidae) - Sun, Yanchun; Meng, Rui; Wang, Yinglun (Zootaxa, 2012)
Neogergithoides gen. nov. is described from China with N. tubercularis sp. nov. as the type species. Morphological structures,male and female genitalia and female internal reproductive organs of the new species are described and illustrated. A key to genera of Hemisphaeriini is provided. The genus is compared to other superficially similar genera.